Co-creation of value in smart ecosystems: past trends and future directions in tourism literature - Díaz, Estrella; Esteban, Águeda; Koutra, Christina; Almeida, Sofia; Carranza, Rocío (Journal of Hospitality and Tourism Technology, 2023)
Purpose: This study aims to present a general approach for understanding and analyzing the thematic evolution of the concept of co-creation in smart environments within the tourism context. Design/methodology/approach: This study performs a co-word analysis with a longitudinal framework that produces strategic diagrams to categorize the detected themes and concepts related to co-creation. Findings: By combining the performance analysis of science mapping, the following clusters are distinguished: information technology, social media and behavior; tourism organizations, management and innovation; co-creation, technology and sharing economy; co-production and hospitality; and Smart tourism, destinations, sustainability and residents. Originality/value: This study provides a valuable tool for tourism scholars and managers to effectively analyze the importance of different themes linked to co-creation in the concept of the smart environment. This research outlines the evolving issues in and around the touchpoints and associated emerging research topics for future research.
Keywords: bibliometrics; clusters; co-creation; smart ecosystems; tourism; Scopus; JCR